2020
DOI: 10.1108/intr-04-2020-0181
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotions shape the diffusion of cancer tweets: toward an integrated social network–text analytics approach

Abstract: PurposeDrawing on the cognitive-functional model of emotions and emotional contagion, the authors aim to examine the role of negative emotions in the diffusion of cancer tweets.Design/methodology/approachUsing an integrated approach of social network and text analytics, the authors analyzed 142,883 cancer tweets from February to March 2018. The roles of negative emotions, emotional contagion, cancer themes and user influence on the diffusion of cancer tweets were examined.FindingsResults indicated that cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 71 publications
(95 reference statements)
2
15
1
Order By: Relevance
“…However, the addition of one or more neutral emotions such as surprise, trust, and anticipation led to lower diffusion results. Looking at the other independent factors, we can see that follower, URL, and media had significant impact on all of the diffusion constructs, as found in other studies [5][45] [44].…”
Section: Findings and Limitationssupporting
confidence: 78%
See 1 more Smart Citation
“…However, the addition of one or more neutral emotions such as surprise, trust, and anticipation led to lower diffusion results. Looking at the other independent factors, we can see that follower, URL, and media had significant impact on all of the diffusion constructs, as found in other studies [5][45] [44].…”
Section: Findings and Limitationssupporting
confidence: 78%
“…Another research by Wang & Wei [43] concluded that anger is positively correlated to information diffusion for cancer-related discussions. Very recent research by Wang and Lee [44] also analyzed the impact of negative emotions on cancer tweet diffusion. Meanwhile, other studies have discovered that negative emotions do not widely circulate general knowledge [25], political [5], or health-related signals [39].…”
Section: Emotions and Information Diffusionmentioning
confidence: 99%
“…Secondly, the emotion communication capacity usually decreased as the emotion tendency changed from positive to negative. Previous studies have shown that positive emotions reduce people’s attention [ 62 , 63 , 80 ] and that disgust and fear spread more widely through social media [ 70 , 71 , 72 ], but the results of this study are not consistent with these notions. This is mainly because food safety is an issue that is close to people’s livelihood.…”
Section: Discussioncontrasting
confidence: 99%
“…Negative emotions mediated the level of misinformation and information transmission [ 58 ]. Compared with neutral emotions, negative emotions that may cause disgust, fear, or happiness are more likely to spread from person to person, and they are spread more widely through social media [ 70 , 71 , 72 ]. Negative emotions tend to cause people to pay more attention, while there is less focus on positive emotions [ 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…As Twitter has evolved to become a widely used and legitimated source of news and information, its use during times of crises has received considerable attention from scholars and practitioners in recent years (Sutton et al, 2020 ). Previous studies have mainly examined three types of message‐related factors influencing crisis information sharing on Twitter, namely, Twitter characteristics such as the inclusion of hashtags and/or hyperlinks (e.g., Son et al, 2020 ; Sutton et al, 2014 , 2020 ; Sutton, Gibson, et al, 2015 ), tweet emotions (Wang & Lee, 2020 ; Xu & Zhang, 2018 ), and tweet content themes (Chew & Eysenbach, 2010 ; Son et al, 2019 ; Sutton, Ben Gibson, et al, 2015 ). Collectively, these message features can be viewed as drivers or barriers of retransmission of crisis information, depending on the specific context.…”
Section: Literature Review and Theoretical Foundationsmentioning
confidence: 99%